Managing severe aggression in frontotemporal dementia. (February 2014) - Powell, Alice; Flynn, Patrick; Rischbieth, Sally; McKellar, Duncan
Objective: The aim of this paper is to present a case and discussion illustrating the limitations in the evidence base to guide practice in relationship to managing severe aggression in people with dementia. It also calls attention to the association between haloperidol use and increased mortality in dementia. Method: Case report and review of the literature. Results: A 60-year-old man with rapidly progressive frontotemporal dementia complicated by severe aggression was managed in specialised psychogeriatric services and high-dose haloperidol was used. This treatment decision was made following literature review, consultation with experts and a detailed risk–benefit analysis. Unfortunately, his physical condition deteriorated swiftly and he died soon after. Conclusions: Haloperidol is associated with increased mortality in patients with dementia. This case exposes the difficulties in managing severe aggression in dementia, with few safe and effective treatment options and a lack of consensus guidance in the area of very severe aggression in dementia.